Energy and Power Demand of Food Production in Space based on Results of the EDEN ISS Antarctic Greenhouse - Zabel, Paul; Vrakking, Vincent; Zeidler, Conrad; Schubert, Daniel (2022)
The EDEN ISS greenhouse is a space-analogue test facility near the German Neumayer III station in Antarctica. The facility is part of the project of the same name and was designed and built since 2015 and eventually deployed in Antarctica in January 2018. The first operational phase of the greenhouse started on February the 7th and continued until the 20th of November 2018. The purpose of the facility is to enable multidisciplinary research on topics related to future plant cultivation on human space exploration missions. Research on food quality and safety, plant health monitoring, microbiology, system validation, human factors, horticultural sciences and resource demand were conducted. Part of the latter were measurements of the electrical energy and power demand. Those measurements were conducted on the facility and subsystem level, which were complemented by determining the demand of single components like LED lamps at different illumination settings. This paper describes the electrical energy and power demand during the experiment season between February and November 2018. Furthermore, the impact of these results on designing and planning future plant cultivation system in space are evaluated.